GPATCH11 variants cause mis-splicing and early-onset retinal dystrophy with neurological impairment - Zanetti, Andrea (2024)
310030_204285s from the Swiss National Science Foundation to C.R. J.M.R. is member of the European Reference Network for Rare Eye Diseases (ERN-EYE), which is co-funded by the Health Program of the European Union under the Framework Partnership Agreement n\u00B0739534. The authors thank the Transgenesis, Neurobehavioral and Metabolism, Necker Bioimage Analysis, Cell Imaging, Histology (Sofian Ameur, Damien Conrozier, and Sophie Berissi), Cytometry, Genomic, and Proteomic platforms for valuable discussions and help. Special thanks go to Nicolas Cagnard for the submission to BioStudies. We acknowledge the sequencing and bioinformatics expertise of the I2BC High-throughput sequencing facility, supported by France G\u00E9nomique (funded by the French National Program \u201CInvestissement d\u2019Avenir\u201D ANR-10-INBS-09. The authors would like to acknowledge all patients and their families for participating in this study. The authors are also grateful to Virginie G. Peter and Raquel Rodriguez for their help throughout the study and to Sitta F\u00F6hr for careful proofreading of the manuscript. This research was made possible through access to the data generated by the France Genomic Medicine Plan 2025 and the authors thank Dr. Marine Lebrun for her help in the genome analysis. Publisher Copyright: © The Author(s) 2024.